Implementación de acabados con drywall como un sistema de construcción no convencional en viviendas de escasos recursos en la parroquia de Amaguaña - Toapanta Mosquera, Juan Emilio (2018)
The new non-conventional constructive technique Drywall shortens the execution time in finishes of a house, Therefore with this method is intended to implement the implementation of Drywall as an unconventional construction system in lowincome housing in the parish of Amaguaña. The project focuses on developing a process that will allow the installation of drywall to give constructive finishing such as lying, walls, partitions that optimize economic resources and labor in a low-income housing. This constructive technique will be shaped in a practical way, with the construction of different architectural elements such as false ceilings, and decorative elements that will allow constructive solutions through joints, joints, anchors. It will not be included in insulation processes, electrical installations, hydrosanitary installations or treatment to external agents, which will put at risk the materials to be installed. The possibility of working with prefabricated elements that guarantee specific characteristics, allows on site work with greater safety and ease.